Patterns of undergraduates' attitude to academic work (2002)
The study was designed to examine the pattern of undergraduate students' attitude to academic work in order to create insight into how they learn. A 23-item Attitude to Academic Work Scale (ATAWS) was administered to 348 undergraduates in three Universities- Ibadan, Ilorin and Olabisi Onabanjo. The findings revealed that undergraduates of both gender, are similar in their pattern of attitude to academic work in many ways, while the few areas of divergent attitudes are indications that the students need re-orientation of attitudes towards academic work. Nevertheless, these findings spell implications for the quality of socialization process that determine personality, the level of motivation and processing of academic information, as well as societal control of means of livelihood. Thus, it was suggested that major stakeholders in tertiary education in Nigeria, should put in place educational policies that are capable of improving the attitudes of Nigerian undergraduates to academic work.